Flow Model Considering the Influence of Low Velocity Non-Darcy Flow and Reservoir Connectivity and its Application. (September 2020) - Li, Meifang; Miao, Zhiguo; Zheng, Xianbao; Li, Min; Jia, Shihua; Wang, Hongwei; Wang, Jiankai
Abstract: During the development of low and ultra-low permeability sandstone reservoir, due to the starting pressure gradient of poor reservoir physical properties, it is difficult to establish effective displacement between oil and water wells, and high voidage replacement ratio and low formation pressure are common phenomena. So it is necessary to analyze the influential factor of high voidage replacement ratio of low and ultra-low permeability reservoir. A one source and one sink flow model considering low velocity non-Darcy flow and unconnected reservoirs was established by using the flow theory of unidirectional flow and radial flow, and the model was solved by numerical method. The results show that the unconnected layers of water well will lead to the increase of invalid water injection; the larger the starting pressure gradient is and the larger the volume proportion of unconnected layer is, the smaller the maximum annual liquid production rate is and the higher the cumulative voidage replacement ratio corresponding to maintaining the maximum liquid production rate is. It is theoretically proved that the existence of unconnected layers and starting pressure gradient are the factors leading to the existence of high voidage replacement ratio in low and ultra-low permeability reservoirs. The study provides a theoretical basis for the adjustment of high-efficiency water injection in reservoirs.